Reasons for disclosure and non-disclosure of HIV diagnosis to children on antiretroviral therapy at the paediatric clinic, Odi Hospital - Mahloko, Johanna Metja (University of Limpopo (Medunsa Campus), 2012)
Background The increased access to HAART and increased survival of perinatally HIV-infected children have given rise to challenges that parents and caregivers face of disclosure of HIV serostatus to their infected children. Given the increased number of children on ART in the country health care providers and caregivers are now faced with the challenge of a population of children who have not been disclosed. The issue of disclosure should be viewed as a great public health concern. Aim and objectives The aim of the study was to determine the socio-demographics of caregivers and children and determine caregivers’ reasons for disclosure and non-disclosure of HIV diagnosis to children on antiretroviral therapy. Methodology: A quantitative descriptive study using researcher administered questionnaires was conducted with a sample of 149 disclosed and non-disclosed caregivers of children aged 4-17 enrolled in an antiretroviral treatment programme of a district hospital. Data were cleaned, coded and captured on Microsoft Excel and analysed in STATA version 10. Results Of 149 caregivers, 97.99% were females, and 2.01% were males, age ranged from 19-81 years with a mean age of 42 years, 25% attained primary education, 51% the grade not completed, 21% completed grade 12, and 3% had a tertiary education, 55.7% were unemployed, 27.3% fully employed, 14% were pensioners, 3% were schooling. Of the 149 children, 58% were girls, 42% boys, aged range of 4-17 years, mean age of 8.3 years, mean diagnosis age was 6 years, mean time on ARVs was 3.1years, and mean disclose age was 9.3 years. Majority (52.3%) children were cared for by mothers, (28.2%) by grandparents, and of the rest (17.4%) by other relatives, only 2% by their fathers. About 38% single orphans having lost their biological mothers, 35% were double orphans. About 39.6% of children were disclosed to and 60.4% not disclosed to. For those children to whom disclosure had been made 52.5% were disclosed to between ages 6-10, 35.6% between ages 11-15, 10.2% between ages 1-5. Reasons for disclosure were varied, and most cited were adhere to medication (36.5%), consistent questioning about disease and medications (36.5%), fear of accidental disclosure (9.5%), prompted by health professionals (7.9%), and child reaching puberty (3.2%). Reasons for non disclosure were also varied, most cited were child was too young to understand the disease, child will tell others, fear of stigma and discrimination, and did not have the skills to disclose Conclusions Prevalence of disclosure was much higher (39.5%) than other findings and there was greater involvement of health care providers in disclosing HIV to children. The study found a low disclosure rate among biological mothers who were in majority in the sample. Adherence to medication and persistent questioning about the disease and medication were the most cited reasons for disclosing HIV to children. Majority of caregivers delayed disclosure fearing that children will tell others because they are still too young to understand the implications of the diagnosis. Fear of stigma and discrimination also influenced disclosure. Caregivers delayed disclosure because they did not have the skills to disclose and explain HIV to children. Recommendations We recommend that disclosure guidelines be developed and healthcare providers trained in disclosure counselling to better advice caregivers on how to disclose to, thus making HIV disclosure to children an integral part of the comprehensive care of children on ART. Strengthening of life skills education programs at school to take into account the situation of children living with HIV Key words: Disclosure, non-disclosure, caregiver, children, ART, South Africa
Thesis (MPH)-- University of Limpopo, 2011
Keywords: Antiretroviral therapy